Penggunaan website Sumbar Travel terhadap pemenuhan kebutuhan informasi wisatawan di Sumatera Barat - Reihan Deski Putra; Sukaesih Sukaesih; Wina Erwina; Lutfi Khoerunnisa (Jurnal Kajian Informasi dan Perpustakaan, 2021)
Travel trends have influenced tourist information to be easily accessed by tourists. Several institutions use digital media a lot in promoting tourism in an area. One of them is the Sumbar Travel website used by the West Sumatera Provincial Tourism Office. This study aimed to determine the use of the Sumbar Travel website to meet the information needs of tourists in West Sumatera through analysis of information content, website usability, appearance, and website navigation systems. This study used correlation quantitative research methods. The study results found that the website's information content contributed to fulfilling the information needs of tourists by presenting attractions, culinary, and cultural activities of West Sumatera, as much as 52.5% and 47.5% were determined by other variables. The website's appearance played an essential role in meeting tourist information needs, which contained tourist objects and photos of West Sumatera tourist attractions, as much as 51% and determined by other variables 49%. The website navigation system played an essential role in meeting tourist information needs by providing various tourist information categories by 29%, and 71% were determined by other variables. The website's usefulness contributed to the fulfillment of tourist information needs by 42.5%, and 57.5% were determined by other variables. This study concludes that there is a significant relationship between the influence of the Sumbar Travel website and meeting the information needs of tourists in West Sumatera.